2020
DOI: 10.23971/jefl.v10i1.1625
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English using a genre pedagogy to Islamic junior high school students

Abstract: This descriptive qualitative study aims to find out how a genre pedagogy is used to teaching the English language. A class consisted of thirty-six students of a public Islamic junior high school was selected purposefully as participants. The data collection involved participant observation, field notes, and documents, in this case, the students' works. The participant observations were conducted in four meetings. During the observations, this study collected the students’ works purposefully. The data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…In the process of teaching foreign languages, due to the lack of a natural language environment, students mainly rely on the classroom language environment, in which they learn foreign languages by retelling, remembering, or imagining some scenes in their minds. e latest "2017 Curriculum" has established three major thematic contexts: "Man and Self, Man and Society, and Man and Nature," and each of these three thematic contexts is divided into more subthematic groups, which are interconnected and inseparable from each other [4,5]. e thematic context of "Man and Self" advocates a correct and healthy lifestyle, which is conducive to students' better understanding, enriching and perfecting themselves and cultivating a correct human attitude; the thematic context of "Man and Society" is conducive to students' forming good social interaction and establishing good interpersonal relationships [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of teaching foreign languages, due to the lack of a natural language environment, students mainly rely on the classroom language environment, in which they learn foreign languages by retelling, remembering, or imagining some scenes in their minds. e latest "2017 Curriculum" has established three major thematic contexts: "Man and Self, Man and Society, and Man and Nature," and each of these three thematic contexts is divided into more subthematic groups, which are interconnected and inseparable from each other [4,5]. e thematic context of "Man and Self" advocates a correct and healthy lifestyle, which is conducive to students' better understanding, enriching and perfecting themselves and cultivating a correct human attitude; the thematic context of "Man and Society" is conducive to students' forming good social interaction and establishing good interpersonal relationships [6].…”
Section: Introductionmentioning
confidence: 99%
“…At the tertiary level of education, studies have used SFL GP to teach academic writing (Emilia & Hamied, 2015;Haerazi & Irawan, 2019;Nagao, 2019). A recent study showed that the SFL GP with an adaptation of rewriting strategy from Reading to Learn activities could be used to teach spoken daily texts of giving instruction, invitations, and asking to Islamic junior high school students (Aunurrahman, et al, 2020). However, a limited study of SFL GP had been found in the scope of the primary level of education (Chaisiri, 2010;Rose, 2015), specifically in Indonesia.…”
Section: Indonesian Journal Of English Languagementioning
confidence: 99%
“…The explicit teaching, scaffolding, and joyful activities are implemented during the application of the four stages of SFL GP that have been used mainly in Indonesia (Aunurrahman et al, 2020). The first stage of SFL GP is building knowledge of the field stage where the YELs are introduced to a theme using relevant texts (van Dijk & Hajer, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations